Economic Democracy Value Erroring through the Establishment of Soe Holding - Negara, Dharma Setiawan; Jened, Rahmi (Migration Letters, 2024)
Economic democracy is an economic system based on the principles of democracy, namely freedom, equality and accountability. In an economic democracy, the roles of the government and the private sector are balanced. The government plays a role in creating a conducive business climate, while the private sector plays a role in driving the economy. The establishment of BUMN holding is one of the government policies in order to increase the role of BUMN in the economy. The purpose of this study is to analyze the misvalues of economic democracy through the establishment of BUMN holding. This research uses qualitative research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and conclusion drawing. The results showed that the formation of BUMN holding is a policy that can improve the efficiency and competitiveness of BUMN. However, the formation of BUMN holding also has the potential to cause mistakes in the value of economic democracy. The government needs to consider the potential for errors in the value of economic democracy in implementing the policy of establishing BUMN holding.